Effects of different mobile phone UMTS signals on DNA, apoptosis and oxidative stress in human lymphocytes. (December 2020) - Gulati, Sachin; Kosik, Pavol; Durdik, Matus; Skorvaga, Milan; Jakl, Lukas; Markova, Eva; Belyaev, Igor
Abstract: Different scientific reports suggested link between exposure to radiofrequency radiation (RF) from mobile communications and induction of reactive oxygen species (ROS) and DNA damage while other studies have not found such a link. However, the available studies are not directly comparable because they were performed at different parameters of exposure, including carrier frequency of RF signal, which was shown to be a critical for appearance of the RF effects. For the first time, we comparatively analyzed genotoxic effects of UMTS signals at different frequency channels used by 3G mobile phones (1923, 1947.47, and 1977 MHz). Genotoxicity was examined in human lymphocytes exposed to RF for 1 h and 3 h using complimentary endpoints such as induction of ROS by imaging flow cytometry, DNA damage by alkaline comet assay, mutations in TP53 gene by RSM assay, preleukemic fusion genes (PFG) by RT-qPCR, and apoptosis by flow cytometry. No effects of RF exposure on ROS, apoptosis, PFG, and mutations in TP53 gene were revealed regardless the UMTS frequency while inhibition of a bulk RNA expression was found. On the other hand, we found relatively small but statistically significant induction of DNA damage in dependence on UMTS frequency channel with maximal effect at 1977.0 MHz. Our data support a notion that each specific signal used in mobile communication should be tested in specially designed experiments to rule out that prolonged exposure to RF from mobile communication would induce genotoxic effects and affect the health of human population. Graphical abstract: Image 1 Highlights: Comparatively analyzed genotoxic effects of UMTS signals at different frequency. Significant role of UMTS carrier frequency (1977 MHz) in inducing DNA damage. No association of UMTS exposure with apoptosis, TP53 mutations and PFG induction. Prolonged exposure to microwave radiation may induce genotoxic effects.